Biomolecule Damage (DNA and Lipid) is Elevated in Patients with Type 1 Diabetes with and without Diabetic Complications - Hannon-Fletcher, Mary P.A.; Weatherup, Colin; O’Kane, Maurice J.; Moles, Ken W.; Barnett, Yvonne A. (Journal of Nutritional Therapeutics, 2014)
There is strong evidence that oxidative stress is involved in the aetiology and pathogenesis of diabetes and its complications. Increased production of reactive oxygen species in vivo can lead to cellular biomolecule damage, such as lipid peroxidation and DNA damage. The aim of this study was to determine the extent of this damage by measuring in vivo antioxidant status, levels of lipid peroxidation, and levels of neutrophil DNA damage in 50 participants with type 1 diabetes and 50 age- and sex-matched, healthy controls. Gylcaemic control (%HbA1c) was relatively good with a group mean of 7.71% which increased to 8.12 % in those with complications. Compared to the control group there were significantly elevated levels of neutrophil DNA damage (% tail DNA, p<0.0001) and plasma MDA levels (p<0.05) in the Type 1 group as a whole, this significance rose to p<0.01 in those with complications. There were significant alterations in markers of antioxidant status including, reduced levels of superoxide dismutase (p<0.0001), uric acid (p<0.05) and Vitamin C (p<0.05) and elevated levels of catalase (p<0.001). These results indicate that even with acceptable glycaemic control significant oxidative damage still occurs and this damage increases, in some indices, with the onset of complications.